Matlamat Pendidikan Moral: Suatu Penilaian Terhadap Matlamat Projek Pendidikan Moral Di Malaysia - Md. Aroff, Abd. Rahman (Penerbit Universiti Sains Malaysia, 1984)
This paper discusses several specific aims of moral education, and appraises the objectives of the Moral Education Project in Malaysia. It is felt that inclusion by the Malaysia Moral Education Project of some of the aims, discussed in this paper, into its existing set of objectives could enhance the comprehensiveness and adequacy of the Project's Moral Education objectives.